A randomized clinical trial to determine effectiveness of driving simulator retraining on the driving performance of clients with neurological impairment. (June 2015) - Mazer, Barbara; Gélinas, Isabelle; Duquette, Josee; Vanier, Marie; Rainville, Constant; Chilingaryan, Gevorg
Introduction: Following a neurological event, returning to driving is an important activity contributing to improved participation within the community. The purpose of this study was to examine the effectiveness of driving simulator retraining on driving in clients with neurological impairment and to examine factors associated with treatment effectiveness. Method: Individuals with non-degenerative brain injury were randomized to either a simulator training or control group. The simulator group received individualized training (16 sessions) using a driving simulator. The control group did not receive intervention. A blind evaluator assessed participants on the DriveAble On-Road Driving Evaluation. Results: There was no significant difference between groups in the proportion of individuals who passed the driving evaluation (Chi 2  = 0.65; p  = 0.42; CI = −0.41 to +0.17). However, participants with moderate impairment who received simulator training were more likely to pass the driving test compared with those in the control group (86% versus 17%; Chi 2  = 6.2; p  = 0.03; CI = −1.00 to −0.30). There were no differences in pass rate according to diagnosis, gender, or for those with severe impairments. Conclusion: Results provide clinicians with preliminary information on the potential clinical usefulness of driving simulator training. While the findings do not support simulator retraining for the group as a whole, they suggest that clients with moderate impairment have the potential to benefit.